Qualifications Framework of Essential Learning Outcomes for Computer Innovation and Digital Industry Professionals - Thamasan Suwanroj; Orawan Saeung; Punnee Leekitchwatana; Kanaporn Kaewkamjan (My University, 2023)
This research aimed to study and analyze the factors of the qualification framework of essential learning outcomes for computer innovation and digital industry professionals. The factors consisted of indicators of essential competencies for undergraduates under the professional qualifications of Computer Innovation and Digital Industry Major based on the context of Nakhon Si Thammarat Rajabhat University (NSTRU). The sample group consisted of all teachers and experts in Computer Science, Computer Engineering, Software Engineering, Information Technology, Business Computer, and Computer Education, covering all undergraduate programs from public institutions of higher education across Thailand. The research instrument was the questionnaire about factors of the qualifications framework of essential learning outcomes for undergraduates in Computer Innovation and Digital Industry Major. The questionnaire used five levels of a rating scale. Content validity and reliability for the scale were 0.96–1.00, and the content validity and reliability for the factor were 0.97–0.99. Second-order confirmatory factor analysis (CFA) was employed for data analysis. The research discovered new knowledge on the list of essential competencies for undergraduates under five factors of the qualifications framework of learning outcomes with 24 indicators. These 24 indicators were separated for each factor: six for Ethical and Moral Development and Knowledge, four for Cognitive Skills, Interpersonal, and Responsibility, Numerical Analysis, and Communication and Information Technology skills, respectively.
Keywords: Higher Education Learning Practices